The Influence of Compensation on Employee Performance at PT Panjunan Sumedang - Fitriyani, Silfi; Rahayu, Melly Sri; Suharna, Suharna; Yudhistira, Reza; Pamungkas, Ridho; Hendyeni, Selly (SINTESA, 2024)
This research aims to examine the influence of compensation variables on employee performance at PT Panjunan Sumedang. The research method used is a quantitative method with a descriptive approach. The sample collection technique used a saturated sampling technique with a sample size of 58 respondents. Data was collected through questionnaires, and data analysis was carried out using validity, reliability and t tests processed with the SPSS 2023 application. The results of the study showed that the Compensation variable had a positive and significant influence on employee performance, with a t value of 5.398 which was greater than the value critical t table is 1.673. Apart from that, the significant value obtained was 0.05. This shows that the hypothesis which states that compensation has a significant effect on employee performance is acceptable